Strategic option pricing - Bieta, Volker; Broll, Udo; Siebe, Wilfried (Economics and Business Review, 2020)
In this paper an extension of the well-known binomial approach to optionpricing is presented. The classical question is: What is the price of an option on therisky asset? The traditional answer is obtained with the help of a replicating portfolioby ruling out arbitrage. Instead a two-person game from the Nash equilibrium of whichthe option price can be derived is formulated. Consequently both the underlying asset’sprice at expiration and the price of the option on this asset are endogenously determined.The option price derived this way turns out, however, to be identical to theclassical no-arbitrage option price of the binomial model if the expiration-date pricesof the underlying asset and the corresponding risk-neutral probability are properlyadjusted according to the Nash equilibrium data of the game.